Impact of Video File Format on Quality of Experience (QoE) of Multimedia Content - Laghari, Asif Ali; He, Hui; Khan, Asiya; Karim, Sajida (3D research, 2018)
Video file formats are used to record, play and store videos according to heterogeneous platforms; devices and online streaming on networks vary by speed. Video formats are different codecs and resolution from each other and also vary in display quality and storage size which also differentiate the quality of experience (QoE) of users. This paper presents the subjective QoE of end user’s for different video file format varied according to resolution quality and bitrate. Videos of most popular formats which are used for online streaming was downloaded from YouTube and stored on the local system for play for subjects to perceive the video quality. Subjective QoE experiments were conducted by questionnaires given to subjects to perceive video quality and assign ratings. Results show high ratings for FLV 240P and WebM 360P for low resolution videos where high ratings for the MP4 video for 720P and 2160P high resolutions. Graphical Abstract